2014
DOI: 10.1177/0193841x14529125
|View full text |Cite
|
Sign up to set email alerts
|

Trying to Raise (Low) Math Achievement and to Promote (Rigorous) Policy Evaluation in Italy

Abstract: Some effects attributable to the intervention have been detected. Moreover, this project shows that a rigorous approach to evaluation is feasible also in a context lacking attention towards evidence-based policies, such the Italian school system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…A possible explanation is that student-related variables may differ more and more complex interaction according to the individual special education teacher's contest than other variables. Individual and school-level intervention plans are needed to strengthen the capacity of teachers so that individual teachers can cope with their situation (Argentin et al, 2014;Caputo & Rastelli, 2014). Third, our results regarding school-related variables indicated that special education teachers' support from school personnel was another variable that was significantly related to their burnout scale (95% CI = [−0.172, −0.065] for emotional exhaustion; 95% CI = [−0.157, −0.122] for depersonalization; 95% CI = [0.127, 0.217] for personnel accomplishment).…”
Section: Implications For Teacher Education and Trainingmentioning
confidence: 99%
“…A possible explanation is that student-related variables may differ more and more complex interaction according to the individual special education teacher's contest than other variables. Individual and school-level intervention plans are needed to strengthen the capacity of teachers so that individual teachers can cope with their situation (Argentin et al, 2014;Caputo & Rastelli, 2014). Third, our results regarding school-related variables indicated that special education teachers' support from school personnel was another variable that was significantly related to their burnout scale (95% CI = [−0.172, −0.065] for emotional exhaustion; 95% CI = [−0.157, −0.122] for depersonalization; 95% CI = [0.127, 0.217] for personnel accomplishment).…”
Section: Implications For Teacher Education and Trainingmentioning
confidence: 99%
“…Further research could include the observation of other variables related to individual, training‐related and organizational dimensions (Baldwin & Ford, ; Bocciardi et al ., ; Diamantidis & Chatzoglou, ; Holton, ; Kontoghiorghes, ) which may reduce, enhance or interact with training outcomes and potentially also with Q4TE scores. With reference to this, also in response to the different limitations already identified, further studies could benefit from longitudinal designs, which can conceptualize the training and its evaluation as a multifactorial process influenced also by time and by what precedes and follows the classroom sessions (Argentin et al ., ).…”
Section: Limitations and Further Researchmentioning
confidence: 97%
“…CBT techniques may be employed to help teachers change the function and impact of negative thoughts (e.g., paranoia) and feelings (e.g., cognitive restructuring and cognitive reappraisal). Second, the intervention should incorporate components of teachers' professional training and development (58,59) that address skills of career adaptability, conflict-resolution, self-efficacy and social-skills training. The intervention should also address workplace bullying in schools, how to identify it and report it and how to effectively manage bullying in schools and prevent it.…”
Section: Practical Recommendationsmentioning
confidence: 99%